If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 1) = 2(x + 1) + -3(x + -5) Reorder the terms: 3(1 + x) = 2(x + 1) + -3(x + -5) (1 * 3 + x * 3) = 2(x + 1) + -3(x + -5) (3 + 3x) = 2(x + 1) + -3(x + -5) Reorder the terms: 3 + 3x = 2(1 + x) + -3(x + -5) 3 + 3x = (1 * 2 + x * 2) + -3(x + -5) 3 + 3x = (2 + 2x) + -3(x + -5) Reorder the terms: 3 + 3x = 2 + 2x + -3(-5 + x) 3 + 3x = 2 + 2x + (-5 * -3 + x * -3) 3 + 3x = 2 + 2x + (15 + -3x) Reorder the terms: 3 + 3x = 2 + 15 + 2x + -3x Combine like terms: 2 + 15 = 17 3 + 3x = 17 + 2x + -3x Combine like terms: 2x + -3x = -1x 3 + 3x = 17 + -1x Solving 3 + 3x = 17 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 3 + 3x + x = 17 + -1x + x Combine like terms: 3x + x = 4x 3 + 4x = 17 + -1x + x Combine like terms: -1x + x = 0 3 + 4x = 17 + 0 3 + 4x = 17 Add '-3' to each side of the equation. 3 + -3 + 4x = 17 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = 17 + -3 4x = 17 + -3 Combine like terms: 17 + -3 = 14 4x = 14 Divide each side by '4'. x = 3.5 Simplifying x = 3.5
| -5x=19 | | 9m+7n-7(3m-4n)= | | 28(x^2-1)=33x | | 39-12w=7-16q | | 4-12=12-4n | | 2*2.5+2=x | | 6y+1=28 | | 2u^2-9u-5=0 | | -6=6-6x | | 7(8)+10=t | | 4w^2+9w=-5 | | 5a-3b+6a+8b= | | 8a=8(4a-[6a+(a-8)])+4 | | 0.05x+0.1(200-x)=0.450x | | 2*.5+2=x | | 3y+6(y-2)+2=26 | | 3x-6=-6x+48 | | (3,4)(-1,-2)= | | 19-(2x+3)=3x+3 | | -4z(z-3)=2-3z | | -16x^2+368x-2035=0 | | 12-3(48)=180 | | 60=4.5x+15 | | 6(2x-6)=-36 | | h/2.5=3.8 | | 7(k-8)+11=-(k-3) | | a=2bc+2bd+2cd | | 11=-d | | 3m^2+14-11m=0 | | x/3-4=x-2 | | -5x-5=-60 | | (x-6)2=23 |